Growth and fecundity of fertile Miscanthus × giganteus (“PowerCane”) compared to feral and ornamental Miscanthus sinensis in a common garden experiment: Implications for invasion - Miriti, Maria N. (Ecol Evol, 2017)
Perennial grasses are promising candidates for bioenergy crops, but species that can escape cultivation and establish self‐sustaining naturalized populations (feral) may have the potential to become invasive. Fertile Miscanthus × giganteus, known as “PowerCane,” is a new potential biofuel crop. Its parent species are ornamental, non‐native Miscanthus species that establish feral populations and are sometimes invasive in the USA. As a first step toward assessing the potential for “PowerCane” to become invasive, we documented its growth and fecundity relative to one of its parent species (Miscanthus sinensis) in competition with native and invasive grasses in common garden experiments located in Columbus, Ohio and Ames, Iowa, within the targeted range of biofuel cultivation. We conducted a 2‐year experiment to compare growth and reproduction among three Miscanthus biotypes—”PowerCane,” ornamental M. sinensis, and feral M. sinensis—at two locations. Single Miscanthus plants were subjected to competition with a native grass (Panicum virgatum), a weedy grass (Bromus inermis), or no competition. Response variables were aboveground biomass, number of shoots, basal area, and seed set. In Iowa, all Miscanthus plants died after the first winter, which was unusually cold, so no further results are reported from the Iowa site. In Ohio, we found significant differences among biotypes in growth and fecundity, as well as significant effects of competition. Interactions between these treatments were not significant. “PowerCane” performed as well or better than ornamental or feral M. sinensis in vegetative traits, but had much lower seed production, perhaps due to pollen limitation. In general, ornamental M. sinensis performed somewhat better than feral M. sinensis. Our findings suggest that feral populations of “PowerCane” could become established adjacent to biofuel production areas. Fertile Miscanthus × giganteus should be studied further to assess its potential to spread via seed production in large, sexually compatible populations.